Tantangan Realitas Profesi Guru Bimbingan Dan Konseling Di Sekolah: Studi Literatur - Finandi Rahmawati; Maya Rahadian Septiningtyas; Lobby Loekmono (Jurnal Pendidikan Sosial Dan Konseling, 2026)
Professional guidance and counseling (BK) teachers now face rapid changes in education that prioritize students' mental health and well-being. However, there is still a wide gap between official rules and the actual practice of school counselors due to complex problems. This study aims to map the real challenges faced by BK teachers and outline a practical adaptation roadmap. Using a qualitative literature study (library research) with content analysis, secondary data were gathered from reputable scientific databases with limited publication years to ensure relevance. The findings show that BK teachers face three main challenges: structural obstacles (qualification mismatches and heavy workloads), cultural obstacles (the negative stigma of BK rooms as places for punishment), and technology gaps (difficulty using digital tools). To solve these issues, this study proposes a four-pillar roadmap: transforming services through cybercounseling and basic AI tools, repositioning the BK image through preventive guidance in class, building strong partnerships (among principals, subject teachers, and parents), and continuing professional development (PKB). In conclusion, improving the quality of BK services requires changes in school policies to better support students in the digital age.